Detection of spike protein in term placentas of COVID-19 vaccinated and/or SARS-CoV-2 infected women - Catharina Bartmann; Vanessa Schmidt; Michael Mörz; Michael Schwab; Monika Rehn; Bettina Blau-Schneider; Achim Wöckel; Ulrike Kämmerer (PLoS ONE, 2026)
Introduction COVID-19 (Corona Virus Induced Disease-19) caused by the SARS-CoV-2 coronavirus can be a serious in pregnancy. Therefore, vaccination with modRNA vaccines was recommended depending on the immunity status for women of reproductive age and pregnant women since 2022. However, there are only preliminary data on transplacental transmission of the virus and modRNA from genetic vaccines so far. Methods The study population included 106 women who have given birth at the Department of Obstetrics and Gynecology, University Hospital of Würzburg during November 2020 to October 2022. In addition to medical data and vaccination history, immunohistochemical examination of the placenta was performed with antibodies against SARS-CoV-2 spike and nucleocapsid proteins. RNAscope in situ Hybridization was used to show RNA detection in positive placental tissues as a proof of concept. Results Altogether, 87% of participants received at least one vaccine dose against SARS-CoV-2 and 56 women (42 vaccinated, 14 not vaccinated) contracted COVID-19. In total, 31 placentas were found positive for the spike protein. Spike positive cells were predominantly Hofbauer cells and trophoblasts. In three cases of vaccinated and then infected woman, an additional nucleocapsid staining was detected, but there was no significant difference in staining pattern in correlation to the vaccine/COVID-19 status. Interestingly, we did not find viral RNA in the investigated samples, but we could show a positive in situ Hybridization of BNT162b2 and S-encoding mRNA-1273 in two individual samples. Discussion The spike protein of SARS-CoV-2 has been be detected in placental Hofbauer and Trophoblast cells as well as villous endothelia after infection and vaccination indicating a possible transplacental transfer or uptake. These findings may suggest a potential for transplacental transfer or cellular uptake; however, the extent, mechanisms, and clinical significance of this phenomenon remain to be fully understood. Clinical trial registration: DRKS00022506.